Attention, Interpretation, Memory (AIM) and Family Resilience as Flourishing Determinants in Early Adult - Tessalonika Sembiring; O.Irene Prameswari Edwina; Jeans Esparanci (Universitas Medan Area, 2023)
This study aims to see whether there is a mechanism for the role of AIM (Attention, Interpretation, Memory) on flourishing with family resilience factors as mediators. Respondents in this study were 241 early adult individuals (aged 20-40 years). Data were collected using a researcher-modified family resilience questionnaire from the Walsh Family resilience Questionnaire (WFRQ). AIM questionnaire consisting of negative thinking and positive thinking. The flourishing questionnaire used was the Mental Health Continuum Short Form (MHC-SF; Keyes 2005, in Hone 2014). The collected data were analyzed using Model 4 of SPSS PROCESS mediation analysis (Hayes, 2018). The results showed that AIM (attention, interpretation, and memory) in the form of both positive thinking and negative thinking provides a direct role in the flourishing of early adult individuals. Positive thinking has a greater direct effect on flourishing than negative thinking on flourishing . Meanwhile, family resilience does not mediate the role of AIM (Positive thinking and negative thinking) on family resilience.